(untitled) (Bangladesh Medical Journal, 2014)
Acute coronary syndrome (ACS) is a set of signs and symptoms due to rupture of a plaque and are a consequence of platelet rich coronary thrombus formation. Platelet parameters especially MPV could be an important and reliable markers in early detection of ACS when other markers are not available. This quasi- experimental study was conducted from September 2011 to August 2012 in the Department of Clinical Pathology, BSMMU, in collaboration with Department of Cardiology, BSMMU and BIRDEM on 79 patients with ACS diagnosed on the basis of clinical history, Electrocardiographic changes and increased cardiac markers especially troponin I with 63 subjects enrolled as control. For determination of platelet parameters, the blood sample was obtained from all patients of ACS before anti-platelet therapy when patient attended in the Cardiac emergency department and on 5th day of ongoing anti-platelet therapy in coronary care unit. The sensitivity, specificity, accuracy, positive and negative predictive value of platelet counts and MPV were 83%, 28.1%, 42.3%, 37.6%, 64% and 90.6%, 49.4%, 64.8%, 51.6%, 89.8% respectively. In our study, we found that MPV had higher sensitivity and specificity in contrast to platelet count. MPV may used as predictor for early detection of ACS and risk stratification when other cardiac biomarkers are negative. DOI: http://dx.doi.org/10.3329/bmj.v42i2.18985 Bangladesh Med J. 2013 May; 42 (2): 45-50